Chronic inguinal pain in elite athletes - Segura Movellan, J. (2001)
Chronic pain in the inguinal region in top-class athletes, and particularly in tennis players, due to the major bursts of effort at points in the game, can be crippling and cause low sports performance. Diagnosis of this condition is difficult and controversial. The most frequently suggested diagnoses are adductor lesions, pubic osteitis and incipient inguinal hernias. The latter is difficult to diagnose by conventional physical exploration of the inguinal region. We conducted ultrasound examinations of the soft parts of the inguinal region in a series of athletes with chronic pain in this region, as well as the relevant explorations to eliminate other diagnoses such as pubic osteitis. The ultrasonograph is performed with associated Doppler, identifying the femoral vessels and symphysis of the pubis. Taking these elements as reference, the musculature of the inguinal region is explored.